INFLUENCE OF BOARD FINANCIAL EXPERTISE ON TAX COMPLIANCE OF NON- FINANCIAL LISTED FIRMS IN NIGERIA - Mathias Gboyega OGUNDEJI (Malete Journal of Accounting and Finance, 2023)
Generating enough tax revenue is still a universal phenomenon due to unabated tax scandals in all jurisdictions. This study sought to provide empirical evidence on the influence of independent board financial expertise(IBFE) on tax compliance of non-financial listed firms in Nigeria using Effective Tax Rate (ETR), Cash Effective Tax Rate (CETR) and Permanent Tax Difference (PERMDIFF) as tax proxies. This study employed explanatory sequential design of mixed method to collect and analyse quantitative and qualitative data and merged the data-sets for interpretation of the results. The study explored data from 68 firms out of 116 non-financial listed firms in Nigeria from 2004 to 2018 while qualitative data was obtained through semi structured interviews on 17 corporate governance agents. A Generalised Least Squares Regression and Discourse analysis were used to analyse the quantitative and qualitative data, respectively. The combined GLS results (Wald Chi square) show that IBFE has a positive statistical significant (ꞵ=0.0000; P<0.05) influence on tax compliance of non-financial listed firms in Nigeria. The qualitative result aligns with the quantitative result. The study concludes that independent financial expertise of the board is of paramount importance to achieving tax compliance in Nigeria. The study recommends that the Financial Reporting Council of Nigeria (FRCN) should promote and implement a policy for the engagement of at least 20% experienced, technically knowledgeable and high integrity independent financial experts on the corporate board for a better monitoring and control of management